Ionic liquids self-assembled micelles for transdermal delivery: characterization, functions and applications - Ziqing Deng; Shuwei Tang; Mingjie Ou; Zhuxian Wang (International Journal of Pharmaceutics: X)
Ionic liquid (ILs) self-assembled micelles (ILs-SAMs) are promising and effective drug delivery systems, which combine the merits of ILs and micelles. Herein, the properties, assembly, functions, and treatments of ILs-SAMs in transdermal drug delivery are summarized. This paper first reviews the fundamental concepts, classifications, assembly mechanisms, characterization techniques, and functional roles of ILs-SAMs. ILs-SAMs are micellar structures formed by the self-assembly of ILs through different intermolecular interactions, and are affected by multiple environmental factors. They possess unique physicochemical properties, endowing them with high stability and effective drug carriers, which could regulate their compositions and structures for flexible and controllable characteristics. Next, the review demonstrates that ILs-SAMs offer remarkable advantages in transdermal delivery, including solubilization enhancement, permeation enhancement, and targeted transdermal delivery. It alters the surface tension and viscosity of permeating substances, facilitates transdermal drug penetration, and utilizes nanoscale properties for precise, targeted delivery. Remarkably, ILs-SAMs were compared with other ILs self-assembled nanoparticles (ILs-SANPs) and polymer micelles, and the former possessed superior properties, including easier self-assembly and higher stability. Lastly, it focuses on their applications in treating skin cancer, arthritis, diabetes, fungal infections, and skin photoaging. Collectively, the novel ILs-SAMs are multifunctional transdermal drug delivery systems used for permeation enhancement, targeted drug delivery and different skin disorders.